Tunable Photocatalytic Activity of PEO-Stabilized ZnO-Polyoxometalate Nanostructures in Aqueous Solution - Bernhardt, Sarah; Düring, Jasmin; Haschke, Sandra; Barr, Maissa; Stiegler, Lisa; Schühle, Patrick; Bachmann, Julien; Hirsch, Andreas; Gröhn, Franziska (Advanced Materials Interfaces, 2021)
The photocatalytic activity and selectivity of novel binary and ternary composite nanostructures from polyethylene oxide-stabilized zinc oxide (PEO-ZnO) with and without polyoxometalate (H-4[Si(W3O10)(4)], POM) are determined in aqueous solution under UV-light. Mono- and di-COOH-end-functionalized PEO polymers are used as surface modifiers, influencing the morphology and stability of the ZnO nanoparticles being synthesized in water. POM acts as an additional versatile photocatalytically active building block resulting in a ternary hybrid structure with tunable photocatalytic activity. Catalytic selectivity is demonstrated by studying photocatalytic dye degradations as model reactions, where the chemical backbone of the dyes and their charge turn out to be the basis for the selectivity. All samples are characterized with dynamic light scattering, transmission electron microscopy, scanning electron microscopy, light microscopy, and zeta-potential measurements. With the functionalized PEOs, large ZnO clusters consisting of leaves are formed while 2-[2-(2-methoxyethoxy) ethoxy] acetic acid (TODA) yields ZnO flower-like structures.
CRIS-Team WoS Importer:2021-07-09